Evaluación de las características físico-químicas de Crescentia cujete (TOTUMO) de diferentes zonas de la provincia de Los Ríos, con la finalidad de proponer su aprovechamiento agroindustrial - Recalde Cedeño, Claudia Estefanía (2015)
This work evaluates the physical and chemical characteristics of Crescentia cujete from different areas in the province of the rivers to get parameters specific to each one of them in order to propose its agro-industrial development. They were used for the respective 24 totumos analysis of which samples were taken from 100 to 300 grams for 12 treatments and 2 repetitions. There were physical-chemical analysis such as: weight, mass, volume and density, pH, acidity, °Brix, dry matter, moisture, ash, fat and protein to determine whether or not there is significant difference between the levels of treatments being studied. In the statistical analysis was applied a experimental design under trifactorial AxBxC. Treatments include Factor: production areas (Vinces and good faith), B-Factor: States of maturation (semi-mature and mature); C Factor: days after harvest (5. 10 And 15 days). For the analysis of data was used the statistical package StatsGraphics Centurion of the University of Massachusetts, jointly for the separation of half of the levels of the treatments she went to the Once you have made the physical analysis- chemical it was concluded that there was a significant difference between the levels of the treatments for chemical analysis and determined how best treatment a1b1c2 (Crescentia cujete zone 2 mature with 15 days of harvesting) as it recorded the best percentages in °Brix of 18.10 ; Grease (13.05 ); Protein(5.67 ) and in relation to the values obtained are recommends the use of fruits of different areas, mature and with 15 days after harvest already that there is a greater concentration of sugars permissible values for use in the industrialization and in regard to the physical analysis showed no significant difference in their treatments. The findings, conclusions and recommendations indicate the satisfaction of having met the objectives and hypotheses raised in the thesis, it will be appreciated in the chapter of results.